(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Environmental pollution caused by anthropogenic factors is a global environmental problem. Heavy metal ions accumulate in the soil and aquatic environment as a result of industrial waste, transport emissions, and improper use of mineral fertilizers. Since they are not biodegradable, they persist in the environment for a long time and are bioaccumulated by plants [4]. In the plant body, these ions disrupt cellular metabolism and lead to disruption of physiological processes. Therefore, studying the mechanisms of heavy metal stress at the cellular level is important for environmental safety and agricultural sustainability.